…Autobiografia reticente… inquietações e narrativas de uma professora de artes - Oliveira, Mayele Maria Souza de (2023)
This work is situated in the field of Visual Arts education, specifically focusing on educational processes in Visual Arts. It goals to highlight the triangular approach and cultural mediation as important paths for art education, exploring visualities and possibilities of visual production between teaching practice and the artistic development of students. Therefore, in this writing, I intend to emphasize my initial experiences as an art teacher at the Centro Educacional Prefeito Eronides Francisco Soares (CEPEFS), based on my concerns, concepts, and reflections regarding my professional identity, cultural mediation, and the triangular approach. I also aim to explore, as an investigative possibility, some of my own visual productions and those of the students, between the years 2021 to 2023, on visits to the Museu de Arte Moderna Aloísio Magalhães (MAMAM) and Engenho Massangana. We start from Barbosa's (2009) concept, who approaches art as an important vector in cultural and social mediation, not only in educational museum spaces but also in the overall formation of the individual. In this context, I highlight as support some discussions on the construction of identity, which, according to Hall (2005), is a reflection of the multiplicities of the modern individual and the society that surrounds him. This discussion is also present in Bauman's (2007) ideas, who bases these multiplicities in the constant processes of weakening and change in the once solidified social and individual structure. Therefore, the entire qualitative writing was methodologically guided by autobiography, which focuses on subjectivity as part of epistemology, considering its individual aspects within society, as evidenced by Ferrarotti (1988) in the biographical method, and by Josso (2004), who highlights the relevance of educational biographies in the individual's formative process. The text is divided into three chapters. The first chapter provides a contextualization of professional identification based on my concerns as an art teacher. In the second chapter, I present cultural mediation anchored in two visiting experiences as an important path for the teaching and learning of arts. Finally, the third chapter visually traces personal productions and those of my students from CEPEFS, which directly and indirectly reflect Barbosa's (1998) triangular approach.